2016
DOI: 10.1097/tme.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Emergency Department Provider Attitudes Toward Patients With Sickle Cell Disease

Abstract: Patients with sickle cell disease frequently seek care in the emergency department. They have reported experiencing negative attitudes from emergency providers. This study was undertaken to evaluate change in emergency provider attitudes toward patients with sickle cell disease over a 2.5-year time period when several educational efforts were ongoing. The General Perceptions about Sickle Cell Disease Patients Scale was used to measure emergency provider attitudes at 2 emergency departments at baseline, 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“… 17 , 18 Details of the project have been published. 17 20 Briefly, the project attempted to optimize the treatment of VOC in the ED using best practices, 1 while monitoring healthcare utilization and psychosocial referral needs and practices. 17 19 In this paper, we report acute healthcare utilization data only (excluding the number of clinic visits).…”
Section: Methodsmentioning
confidence: 99%
“… 17 , 18 Details of the project have been published. 17 20 Briefly, the project attempted to optimize the treatment of VOC in the ED using best practices, 1 while monitoring healthcare utilization and psychosocial referral needs and practices. 17 19 In this paper, we report acute healthcare utilization data only (excluding the number of clinic visits).…”
Section: Methodsmentioning
confidence: 99%
“…Nurses' negative attitude can be explained by that nurses spending more time with sickle cell patients. 16,18 Other factors that may also contribute to nurses' negative attitudes include: they are the first responders to the patients' complaints, patients are blaming them for poor pain control, verbal abuse from the patients, and less participation in educational activities. 18 Moreover, nurses thought that sickle cell patients complain more than other patients and they do not use analgesics appropriately.…”
Section: Et Almentioning
confidence: 99%
“…16,18 Other factors that may also contribute to nurses' negative attitudes include: they are the first responders to the patients' complaints, patients are blaming them for poor pain control, verbal abuse from the patients, and less participation in educational activities. 18 Moreover, nurses thought that sickle cell patients complain more than other patients and they do not use analgesics appropriately. 19 However, this finding does not match what Ratanawongsa et al, 20 had concluded, by using different scale they found that nurses had a more positive attitude toward sickle cell patients than other healthcare providers.…”
Section: Et Almentioning
confidence: 99%
See 2 more Smart Citations